A Review of the Network Meta-Analysis and Psoriasis Management (Actualité dermatologique au Canada, 2025)
Clinical trials are the gold standard for evaluating safety and efficacy of new therapeutics and guiding our treatment decisions. However, with the rapid development of new therapeutics in dermatology, we increasingly need additional tools to inform our overall approach to patient care. Previously, meta‐analyses were used to evaluate the results of several randomized controlled trials (RCTs). However, they were limited to comparing 2 interventions at a time. Recently, network meta‐analysis (NMA) has emerged as a new tool allowing simultaneous comparison of 3 or more interventions by incorporating both direct comparisons from head‐to‐head trials and indirect evidence drawn from studies that share a common comparator (e.g. placebo or active control).